FORECASTING SIMULATION OF INDONESIA COVID-19 CONFIRMED CASES - Amanda Adityaningrum; Herlina Jusuf (Gorontalo State University, 2022)
COVID-19 is an infectious disease caused by a type of coronavirus. The various policies that have been implemented have not had a sufficient effect in controlling the spread of the disease. Beside implementing health protocols, other policies are needed. A policy that begins with planning after seeing a picture of conditions in the future. The description of conditions in the future can be done by running a time series modelling. The purpose of this research is to perform time series modelling to predict the number of Indonesia COVID-19 Confirmed Cases. Secondary data is used for modelling the time series. Data contains the number of positive confirmed cases of COVID-19 from January 2021 to December 2021. The number of observations in this research is 12 observations. Quantitative forecasting using the Box-Jenkins procedure is used in this research. The stages of the Box-Jenkins procedures are: (1) Data Pre-processing and Identification of Stationary Models; (2) Estimated Parameter Model; (3) Diagnostic Check and Selection of the Best Model; and (4) Forecasting or Prediction Simulation for the Model. Based on the results of research and evaluation of time series modelling, the following conclusions were drawn: (1) The model used for forecasting or prediction simulations was ARIMA (0,0,1); (2) ARIMA model (0,0,1) fulfils the assumption model which has random error; and (3) The number of COVID-19 cases in Indonesia in January is estimated to be 172,378 people and 286,986 people in February and March.AbstrakCOVID-19 adalah penyakit menular yang disebabkan oleh jenis coronavirus. Berbagai kebijakan yang diterapkan belum memiliki efek yang cukup untuk mengatasi penyebaran penyakit. Sehingga diperlukan kebijakan selain dari sisi penerapan protokol kesehatan, yang hendaknya diawali dengan perencanaan yang dibuat setelah melihat gambaran kondisi di masa yang akan datang. Gambaran kondisi di masa yang akan datang dapat dilakukan dengan pemodelan time series. Tujuan penelitian ini, yaitu untuk melakukan pemodelan deret waktu untuk meramalkan jumlah kasus terkonfirmasi positif COVID-19 di Indonesia. Data deret waktu yang digunakan pada penelitian ini merupakan data sekunder, berisi tentang jumlah kasus terkonfirmasi positif COVID-19 sejak bulan Januari 2021 sampai dengan Desember 2021. Sehingga jumlah pengamatan pada penelitian ini sebanyak 12 pengamatan (dalam bulan). Analisis yang digunakan adalah pemodelan deret waktu (peramalan kuantitatif dengan prosedur Box-Jenkins. Tahapan prosedur Box-Jenkins, berupa: (1) Pre-processing Data dan Identifikasi Model Stasioner; (2) Estimasi Parameter Model; (3) Diagnostic Check dan Pemilihan Model Terbaik; dan (4) Aplikasi Model untuk Simulasi Peramalan atau Prediksi. Berdasarkan hasil penelitian dan evaluasi pemodelan deret waktu, diperoleh kesimpulan sebagai berikut: (1) Model yang digunakan untuk simulasi peramalan atau prediksi adalah ARIMA (0,0,1); (2) Model ARIMA (0,0,1) memenuhi asumsi model yang memiliki error random; dan (3) Jumlah kasus COVID-19 di Indonesia pada bulan Januari diperkirakan akan sebanyak 172.378 jiwa dan 286.986 jiwa pada bulan Februari dan Maret.